Analisis Pertumbuhan Fase Superkonduktor BSCCO-2212 dan BPSCCO-2212 Akibat Variasi Suhu Sintering Menggunakan Metode Pencampuran Basah - Pulung Karo Karo; Risky Putra Ramadhan; Suprihatin Suprihatin; Yanti Yulianti (Journal of Energy, Material, and Instrumentation Technology, 2021)
The research was conducted to determine the effect of sintering temperature on the level of purity of the superconducting phase BSCCO-2212 and BPSCCO-2212 using the wet mixing method. Sintering was carried out for 20 hours with variations in sintering temperature: 825, 830, 835 and 840°C. XRD results showed that the phase purity level increased until it reached the optimum point at 835°C sintering temperature and then decreased at 840°C. The highest volume fraction of the BSCCO-2212 sample was obtained at a sintering temperature of 835°C at 71.09% and the highest degree of orientation was obtained at a sintering temperature of 830°C at 26.44%. In the BPSCCO-2212 sample, the highest volume fraction was obtained at a sintering temperature of 835°C at 52.59% and the highest degree of orientation at a sintering temperature of 830°C at 43.49%. The results of the comparison of BSCCO-2212 and BPSCCO-2212 samples showed that the BPSCCO-2212 sample had a higher level of phase purity than BSCCO-2212.